The prevalence of sickle cell trait in Division I university athletics programs. Issue 4 (1st October 2020) - Hirschhorn, Rebecca M.; Cadet, Danielle; Delus, Rodain; Phillips, Jessica; Murphy, Tenley E.; Haggard, Clinton; Razayeski, Jerome; Yeargin, Susan
ABSTRACT: Objectives : To determine the prevalence of student-athletes with sickle cell trait (SCT) and describe their demographics, prior knowledge of status, and hemoglobin (Hb) profile. Methods : A retrospective chart review was conducted at two National Collegiate Athletic Association Division I universities. Participants were student-athletes during the 2010/11-2018/19 academic years. The independent variable was SCT status. Main outcome measures included actual prevalence of SCT positive student-athletes, sex, race, sport, prior knowledge of personal and family history SCT status, and Hb profile (HbA, HbA2, HbS, HbF, HbC) proportions. Results : Fifty-three SCT positive student-athletes (13.2 ± 2.0 per academic year) were identified, accounting for ~1% of the student-athlete population annually. The majority were Black/African-American (n = 49, 100.0%; 4 missing) and males (n = 44, 83.0%). Football had the majority (n = 28, 52.8%) of SCT student-athletes. Most student-athletes were unaware of their SCT status (n = 33, 62.3%). There was no difference between actual and expected prevalence of SCT student-athletes overall and by race in any academic year (p > 0.05). Results of Hb electrophoresis testing were available for 44 (83.0%) student-athletes. Average values for HbA, HbA2, HbS, HbF and HbC were 58.54 ± 4.26%, 3.42 ± 0.53%, 37.99 ± 4.60%, 0.17 ± 0.68% and 0.00 ± 0.00%, respectively. Conclusions : Student-athletes with SCT were a small proportion of the student-athlete population. The majority of SCT student-athletes had no prior knowledge of personal or family history; therefore, it is insufficient to rely on self-reported history. No difference was found between actual and expected prevalence of SCT student-athletes. Due to high proportion of student-athletes who are unaware of their SCT status, institutions should facilitate SCT screening with confirmatory testing for all student-athletes to prevent missed identification of those with SCT.